2021
DOI: 10.1111/jocn.15794
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of distress, its associated factors and referral to support services in people with cancer

Abstract: Aims and objectives: To (i) characterise prevalence of distress amongst people diagnosed with cancer, (ii) determine factors associated with increasing distress, (iii) describe reported problems for those with clinically significant distress and (iv) investigate the factors associated with referral to support services. Background: International studies report a high prevalence of clinically significant distress in people with cancer. Australian studies are notably lacking. Additionally, clinicians still do not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…This study's procedures followed the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) checklist (Von Elm et al, 2007 ) (Data S1 ). A comprehensive description of the methods is presented elsewhere (Kirk et al, 2021 ). Briefly, people affected by cancer are typically referred to the CCWA Information and Support Line service by a CCWA representative or health professional (Cancer Nurses or General Practitioners).…”
Section: Methodsmentioning
confidence: 99%
“…This study's procedures followed the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) checklist (Von Elm et al, 2007 ) (Data S1 ). A comprehensive description of the methods is presented elsewhere (Kirk et al, 2021 ). Briefly, people affected by cancer are typically referred to the CCWA Information and Support Line service by a CCWA representative or health professional (Cancer Nurses or General Practitioners).…”
Section: Methodsmentioning
confidence: 99%
“…Information about cancer support services was a common need and tended to be lacking for many rural cancer survivors, particularly information about psychological and emotional support. 22,34,38,44,45,[53][54][55] In one survey study with 1071 cancer survivors, participants living in moderately to highly accessible areas were between two and four times more likely to receive a referral to an emotional support service than those from remote and very remote areas. 55 In another study, 82 rural men with genito-urinary cancer were surveyed and over one-third were not aware of the various psychological and counselling services available to them.…”
Section: Psychosocial Supportmentioning
confidence: 99%
“…22,34,38,44,45,[53][54][55] In one survey study with 1071 cancer survivors, participants living in moderately to highly accessible areas were between two and four times more likely to receive a referral to an emotional support service than those from remote and very remote areas. 55 In another study, 82 rural men with genito-urinary cancer were surveyed and over one-third were not aware of the various psychological and counselling services available to them. 45 One study identified information related to mental health, including relaxation, managing stress, and fear of recurrence, as being in the top three ranked supportive care needs for a sample of 35 rural cancer survivors and their family and friends.…”
Section: Psychosocial Supportmentioning
confidence: 99%
“…It is prevalent at different time points in fighting the illness among cancer patients. Measured by the distress thermometer, psychological distress is suffered by 25.3% to 71.7% of breast cancer patients [ 6 ], 49.04% of lung cancer [ 7 ], and 35% to 91% of patients with different cancer types [ 8 10 ]. An increasing emphasis is placed on the psychological distress experienced by cancer populations.…”
Section: Introductionmentioning
confidence: 99%